2020
DOI: 10.3390/ani10091667
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of XX SRY-Negative Sex Reversal Dogs

Abstract: Impaired fertility associated with disorders of sex development (DSDs) due to genetic causes in dogs are more and more frequently reported. Affected dogs are usually of specific breeds thus representing a cause of economic losses for breeders. The aim of this research is to report the clinical, cytogenetic and molecular genetic findings of four XX SRY-negative DSD dog cases. All the subjects showed a female aspect and the presence of an enlarged clitoris with a penis bone. Morphopathological analyses performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Some DSD dogs may have chromosome abnormalities (sex chromosome DSD), as described above, but the majority of cases have a normal chromosome set described as XX DSD or XY DSD. Sex chromosomes are usually identified in such cases by Giemsa staining, karyotyping of R-banded chromosomes, or FISH with chromosome-specific probes ( Figure 3 ) [ 32 , 59 , 60 , 61 ].…”
Section: Cytogenetic Characterization Of Other Forms Of Dsd Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some DSD dogs may have chromosome abnormalities (sex chromosome DSD), as described above, but the majority of cases have a normal chromosome set described as XX DSD or XY DSD. Sex chromosomes are usually identified in such cases by Giemsa staining, karyotyping of R-banded chromosomes, or FISH with chromosome-specific probes ( Figure 3 ) [ 32 , 59 , 60 , 61 ].…”
Section: Cytogenetic Characterization Of Other Forms Of Dsd Casesmentioning
confidence: 99%
“…Since the resolution of the hybridization signals on metaphase chromosomes is not sufficient to detect SOX9 gene triplication, interphase nuclei were examined ( Figure 5 ) [ 64 ]. It should be mentioned that molecular techniques such as MLPA (Multiplex Ligation-dependent Probe Amplification) and a-CGH (array Comparative Genome Hybridization) have also been employed for the identification of this CNV [ 60 , 61 , 62 ].…”
Section: Cytogenetic Characterization Of Other Forms Of Dsd Casesmentioning
confidence: 99%
“…Moreover, the minimum critical region associated with gonadal development, approximately a 67-kb region located 584-517 kb upstream of SOX9, was confirmed to induce SOX9 overexpression in female-to-male sex reversal [43]. Regulatory elements in the duplication region might enhance SOX9 expression through complex mechanisms [45]. It was suggested that changes in SOX9 expression, resulting from disruptions in some regions upstream of SOX9, could be important in the 46,XX testicular disorder of sexual development.…”
Section: Discussionmentioning
confidence: 90%
“…Presence of SRY gene results in activation of genes, including SOX9, triggering 'male' development pathway toward formation of testes with internal and external masculinization. 4 Reports of XY sex reversal in dogs are rare. 5,6 Conversely, reports of XX sex reversal in dogs are more common.…”
Section: Introductionmentioning
confidence: 99%